Reactive Astrocytosis in a Mouse Model of Chronic Polyamine Catabolism Activation - Chiara Cervetto; Monica Averna; Laura Vergani; Marco Pedrazzi; Sarah Amato; Simone Pelassa; Stefano Giuliani; Francesca Baldini; Guido Maura; Paolo Mariottini; Manuela Marcoli; Manuela Cervelli (Biomolecules, 2021)
Background: In the brain, polyamines are mainly synthesized in neurons, but preferentially accumulated in astrocytes, and are proposed to be involved in neurodegenerative/neuroinflammatory disorders and neuron injury. A transgenic mouse overexpressing spermine oxidase (SMOX, which specifically oxidizes spermine) in the neocortex neurons (Dach-SMOX mouse) was proved to be a model of increased susceptibility to excitotoxic injury. Methods: To investigate possible alterations in synapse functioning in Dach-SMOX mouse, both cerebrocortical nerve terminals (synaptosomes) and astrocytic processes (gliosomes) were analysed by assessing polyamine levels, ezrin and vimentin content, glutamate AMPA receptor activation, calcium influx, and catalase activity. Results: The main findings are as follows: (i) the presence of functional calcium-permeable AMPA receptors in synaptosomes from both control and Dach-SMOX mice, and in gliosomes from Dach-SMOX mice only; (ii) reduced content of spermine in gliosomes from Dach-SMOX mice; and (iii) down-regulation and up-regulation of catalase activity in synaptosomes and gliosomes, respectively, from Dach-SMOX mice. Conclusions: Chronic activation of SMOX in neurons leads to major changes in the astrocyte processes including reduced spermine levels, increased calcium influx through calcium-permeable AMPA receptors, and stimulation of catalase activity. Astrocytosis and the astrocyte process alterations, depending on chronic activation of polyamine catabolism, result in synapse dysregulation and neuronal suffering.